Short term e-bicycle riding results in favorable cardiometabolic shifts in moderately active adults - Helaine M. Alessio; Kevin D. Ballard; Paul T. Reidy; Katie M. Hayward; Alexandra M. Bagg; Rachel A. Cooley; Michael J. O’Connell; Alexander H. K. Montoye; Kyle L. Timmerman (European Journal of Applied Physiology, 2024)
Purpose Electric bikes (EB) are a form of active transportation with demonstrated health benefits. The purpose of this study was to determine the influence of riding an EB for one week on indices of cardiometabolic health in middle-aged adults. Methods Adults (n = 22; age = 57.1 ± 11.3 year; BMI = 27.7 ± 4.9) participated in a 2 week study. During Week 1, participants were instructed to continue regular activities. Starting Week 2 participants were provided an EB to ride at least 3 days for a minimum of 30 min·day −1 . Physical activity (PA) and glucose were measured continuously. Body composition, blood lipids, glucose, insulin, hemoglobin A1c (HbA1c), plasma endothelin-1 (ET-1), and carotid-femoral pulse wave velocity (cf-PWV) were measured on days 1 and 14.Data and Statistical analyses or Statistics. Each participant served as their own control. Paired t-tests compared dependent variables between week 1 (without EB) and week 2 (with EB). Results When provided an EB for one week, moderate to vigorous PA increased by 6–9 min·day −1 (P < 0.05) and sedentary time decreased by ~ 77 min·day −1 (P < 0.05). Data from 24 h continuous glucose monitoring showed the percentage of time in healthy range (70–120 mg·dl −1 glucose) increased (P < 0.05) from week 1 to week 2. Compared to day 1, cf-PWV was lower at day 14 (P < 0.05) following one week of riding an EB. Conclusion Moderately-active, middleaged adults showed improved continuous glucose regulation and lower central arterial stiffness following one week of riding an EB.